تقويم تعليم اللغة العربية للناطقين بلغات أخرى إعداد : أنا أخيت - Achoita, Ana (At-Tuhfah : Jurnal Studi Keislaman, 2019)
Abstract : “Evaluation is a planned process of activities to find out and ascess the state of an object using certain instruments so that conclusions are obtained in the context of decision making. This evaluation includes the curriculum, learning process, abilities, and methods. The evaluation in learning arabic aims to find out the assesment of arabic learning which includes four skills namely listening, speaking, reading and writing”